Lords of the land, lords of the sea; Conflict and adaptation in early colonial Timor, 1600-1800 - Hägerdal, Hans (Verhandelingen van het Koninklĳk Instituut voor Taal-, Land- en Volkenkunde, 2012)
European traders and soldiers established a foothold on Timor in the course of the seventeenth century, motivated by the quest for the commercially vital sandalwood and the intense competition between the Dutch and the Portuguese. Lords of the land, lords of the sea focuses on two centuries of contacts between the indigenous polities on Timor and the early colonials, and covers the period 1600-1800. In contrast with most previous studies, the book treats Timor as a historical region in its own right, using a wide array of Dutch, Portuguese and other original sources, which are compared with the comprehensive corpus of oral tradition recorded on the island. From this rich material, a lively picture emerges of life and death in early Timorese society, the forms of trade, slavery, warfare, alliances, social life, and so forth. The investigation demonstrates that the European groups, although having a role as ordering political forces, were only part of the political landscape of Timor. They relied on alliances where the distinction between ally and vassal was moot, and led to frequent conflicts and uprisings. During a slow and complicated process, the often turbulent political conditions involving Europeans, Eurasians, and Timorese polities, paved the way for the later division of Timor into two spheres of roughly equal size. Hans Hägerdal (1960) is a Senior Lecturer in History at the Linnaeus University, Sweden. He has written extensively on East and Southeast Asian history. Among his publications is Hindu rulers, Muslim subjects: Lombok and Bali in the seventeenth and eighteenth centuries (2001).